Words and dictionaries from the British Isles in historical perspective - Considine, John (John P.); Iamartino, Giovanni (Cambridge Scholars Pub., 2007)
Words and dictionaries from the British Isles in historical perspective brings together a wide range of current work on English-language lexicography and lexicology by a team of twelve contributors working in England, continental Europe, and North America. Fredric Dolezal's opening essay offers a provocative discussion of how the history of English lexicography has been, and might in the future be, written. The next four papers deal with the medieval and early modern periods: Carter Hailey i ...